DO INVESTMENT DECISIONS MODERATE THE EFFECT OF CAPITAL STRUCTURE, PROFITABILITY, FIRM SIZE, AND DIVIDEND POLICY ON FIRM VALUE? EVIDENCE FROM IDX MINING COMPANIES - Rani Raharjanti; Sahra Mawarseta; Sri Murtini; Mardinawati Mardinawati (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2025)
The mining sector plays a vital role in Indonesia’s national economy, making its financial performance an important subject for deeper analysis through multiple financial indicators. This study investigates the effects of capital structure, profitability, firm size, and dividend policy on firm value, with investment decisions introduced as a moderating variable. The sample consists of 26 mining companies listed on the Indonesia Stock Exchange during the 2021–2024 period, selected using purposive sampling, resulting in 104 firm-year observations. Data were analyzed using multiple linear regression and moderated regression analysis with SPSS version 26. The findings reveal that capital structure has no significant impact on firm value. In contrast, profitability exerts a significant positive effect, while firm size and dividend policy both show significant negative effects. Regarding moderation, investment decisions do not moderate the relationship between capital structure and firm value but negatively moderate the effect of profitability, strengthen the effect of firm size, and negatively moderate the effect of dividend policy. These results provide new insights into the dynamics of financial decision-making in Indonesia’s mining sector and highlight the nuanced role of investment choices in shaping firm value.